The Stakeholder Analysis Of Batik Komar CSR Programs In Cirebon Batik Industry - Akhmad, Eggy Saeful; Rudito, Bambang (Journal of Business and Management, 2019)
Batik is a traditionally cloth and also used in traditional matra, has a variety of decorative patterns and patterns that make use of dye technique with batik wax as a material of color barrier with a variety of distinctive ornamental patterns. One of company batik producers nationally known in foreign countries is Batik Komar Batik Komar was founded in 1998 by Dr. Komarudin Kudiya, M.Ds and his wife, Hj. Nuryanti Widya (Yeyen) In Bandung. As a well-known batik company, Batik Komar definately carries out its social responsibility through CSR program. Researcher saw that the CSR Komar program greatly helped the development of Cirebon batik industry in particular. Researcher sees that this phenomenon has an opportunity to help improve the development of the batik industry in general, where companies and actors in the batik industry in general have not been able to implement CSR programs that can provide significant benefits to related industries. The researcher will conduct the research through data from secondary data, in-depth interview, and Forum Discussion Group. The data analysis will use Stakeholder identification, Stakes, Opportunities and Challenges, Responsibility Matrix, and Mapping Process. The result of this research is that several CSR Programs which has been conducted influenced several relevant stakeholders, but evaluation and adjustments still have to be conducted to several CSR Programs. The author recommends the recommended stratergy for each stakeholders.Keywords: Stakeholder Analysis, Batik Industry, Coorporate Social Responsibillity, Batik Cirebon